(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Among alternative fuels for diesel engines, biodiesel is the most attractive. This study’s biodiesel is made from locally renewable sunflower oil. Also, biodiesel is a clean and environmentally acceptable alternative to regular diesel. Compared to pure diesel, the biodiesel mixes (B20, B50, and B100) increased the brake specific fuel consumption (BSFC). The findings show that biodiesel mixes lowered brake thermal efficiency (BTE) and exhaust gas temperatures (EGT) during B20, B50, and B100 combustion. The exhaust gas temperature and BSFC increased with engine load and speed. The research showed that as compared to diesel, biodiesel blends lowered PM concentrations. Furthermore, compared to petroleum diesel, B20, B50, and B100 decreased PM concentrations by 16.847, 28, and 43.34 percent. The findings show that the oxygen content in biodiesel reduces PM concentrations.